Financial Services of the BIESS and its Economic Impact on Students of the University of Guayaquil, 2022-2023. - Bravo Carrasco, Alex; Rosillo Toro, Willian; Belén Chávez, María (Conexiones UG, 2025)
The lack of knowledge about BIESS financial services and their connection to financial education motivated this research, focused on students from the University of Guayaquil during the 2022-2023 period. The main objective was to analyze the economic impact of these services on this student population. A mixed approach was adopted, combining qualitative and quantitative techniques; in the qualitative phase, the students’ perceptions were explored in their natural context, while the quantitative phase employed structured questionnaires to collect data. The results showed that the lack of financial education affects students’ ability to make sound financial decisions, leading to excessive debt and limited use of available financial services. In contrast, proper financial education helps identify basic needs, encourages savings, reduces unnecessary spending, and promotes investments with calculated risks. It is concluded that implementing financial education programs at the University of Guayaquil is essential to improving students’ financial decisions, helping them manage their resources effectively and build a more stable economic future.
Keywords: Financial education; financial services; student economic management; debt and savings